Peran Guru Dalam Meningkatkan Literasi Budaya Dan Kewargaan Siswa Sekolah Dasar - Linda Cibya Rahmawati; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
In the industrial era 4.0, literacy is considered an essential need for every human being to meet the needs of daily life. Education plays the first and main role in the progress of the nation and the State of Indonesia, Indonesia is known as an archipelagic country, this makes Indonesia has a diversity of tribes, races and groups that have many cultures. With the current of globalization that continues to grow, the younger generation is less interested in traditions and culture The process of implementing cultural and civic literacy is among them through the process of traditional game activities carried out by students as a form of cultural literacy activities. In order for the implementation of cultural and civic learning to take place effectively and efficiently, teachers and students in schools must take various steps, such as having school policies that affirm the importance of cultural and civic knowledge, which will affect cultural and civic learning.